FIDIC līguma paraugu izmantošanas tiesiskie aspekti Latvijā - Šarafutdinova, Valentīna (Latvijas Universitāte, 2010)
Работа посвящена изучению юридических аспектов применения строительных договоров FIDIC на территории Латвийской Республики, необходимость применения которых связанна с глобализацией рыночных отношений. Различия в законодательных нормах и необходимость предоставления одинаковых условий для коммерческой деятельности всем членам Евросоюза требует унифицированного подхода к созданию таких строительных договоров, каковым является FIDIC. В то же время существует мнение, что FIDIC договора не являются успешным выбором при заключении договорных обязательств. Целью данной работы стало изучение возможностей FIDIC договоров в свете Латвийского законоk

This paper „Legal aspects of using FIDIC contracts drafts in Latvia” explores the legal aspects of applying FIDIC construction contracts in the territory of the Republic of Latvia, the necessity of which is caused by the globalisation of market relations. The differences in legislative regulations and the need to provide equal conditions for commerce to all members of the EU calls for a unified approach to creating construction contracts, such as FIDIC. At the same time another position maintains that FIDIC contracts are not a very successful choice for outlining liabilities in construction. The goal of this paper is to study the opportunities that FIDIC contracts offer in the light of the Latvian legislation and to offer arguments against their use. Part one provides an in-depth analysis and author’s conclusions regarding the essence of FIDIC contracts, as well as the necessity, as per conditions of FIDIC contracts, to employ an individual for construction work for whom there are no provisions in the Latvian legislation. Part two provides the author’s comparison of the liabilities of various participants of construction whose presence is outlined by the Latvian legislative regulations, as well as the competence and functions of the individual to be employed as per FIDIC contracts, and draws conclusions about the inexpedience of overlap in their functions. In Part 3, the final part of the paper, the author takes into account the necessity to comply with the requirements set by the European Union and studies the possibilities to abandon FIDIC contracts and preserve the local system of relations in construction.
Legal aspects of using FIDIC contracts drafts in Latvia
Keywords: Tiesības